2012
DOI: 10.1121/1.4740482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fundamental-frequency and sentence-onset differences on speech-identification performance of young and older adults in a competing-talker background

Abstract: This study investigated the benefits of differences between sentences in fundamental frequency (F0) and temporal onset for sentence pairs among listener groups differing in age and hearing sensitivity. Two experiments were completed with the primary difference between experiments being the way in which the stimuli were presented. Experiment 1 used blocked stimulus presentation, which ultimately provided redundant acoustic cues to mark the target sentence in each pair, whereas Experiment 2 sampled a slightly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 79 publications
1
32
1
Order By: Relevance
“…In addition to a large body of work investigating speech perception difficulties in older adults (Busey, Craig, Clark, & Humes, 2010; Fogerty, Humes, & Kewley-Port, 2010; Humes, 2007; Humes, Burk, Coughlin, Busey, & Strauser, 2007; Humes, Kewley-Port, Fogerty, & Kinney, 2010; Lee & Humes, 2012), Humes and colleagues have extensively studied the effects of word-based auditory training on speech perception in older adults (Burk & Humes, 2007, 2008; Burk, Humes, Amos, & Strauser, 2006), and have demonstrated that training of words in noise generalizes to unfamiliar talkers and persists for at least 6 months (Burk & Humes, 2008). …”
Section: Auditory Trainingmentioning
confidence: 99%
“…In addition to a large body of work investigating speech perception difficulties in older adults (Busey, Craig, Clark, & Humes, 2010; Fogerty, Humes, & Kewley-Port, 2010; Humes, 2007; Humes, Burk, Coughlin, Busey, & Strauser, 2007; Humes, Kewley-Port, Fogerty, & Kinney, 2010; Lee & Humes, 2012), Humes and colleagues have extensively studied the effects of word-based auditory training on speech perception in older adults (Burk & Humes, 2007, 2008; Burk, Humes, Amos, & Strauser, 2006), and have demonstrated that training of words in noise generalizes to unfamiliar talkers and persists for at least 6 months (Burk & Humes, 2008). …”
Section: Auditory Trainingmentioning
confidence: 99%
“…Suboptimal working memory (especially in older individuals) is associated with reduced speech recognition ability in adverse listening situations (Akeroyd, 2008;Anderson, White-Schwoch, Parbery-Clark, & Kraus, 2013;Desjardins & Doherty, 2013;Humes, Lee, & Coughlin, 2006;Koelewijn, Zekveld, Festen, Rönnberg, & Kramer, 2012;Lee & Humes, 2012). There is also evidence that age-related changes in processing speed are related to a decline in speech perception performance in noise for older adults (Tun et al, 2002;Tun & Wingfield, 1999;Woods, Kalluri, Pentony, & Nooraei, 2013).…”
mentioning
confidence: 93%
“…Background noise makes communication in many situations difficult for older listeners, especially when this noise consists of voices of other talkers (e.g., Desjardins and Doherty, 2013; Helfer, Chevalier, and Freyman, 2010; Helfer and Freyman, 2008, 2014; Humes and Coughlin, 2009; Humes et al, 2006; Lee and Humes, 2012; Rossi-Katz and Arehart, 2009; Tun and Wingfield, 1999). Competing speech situations require individuals to use both peripheral and cognitive resources in order to communicate successfully, as the multiple speech sources must be segregated, messages not of interest must be ignored, and attention often needs to be switched mid-conversation.…”
Section: Introductionmentioning
confidence: 99%